2022
DOI: 10.4102/hsag.v27i0.1992
|View full text |Cite
|
Sign up to set email alerts
|

Student to midwife transition: Newly qualified midwives’ experiences in Limpopo province

Abstract: Background: Regardless of educational pathway, the transition from student to the registered midwife is a topic of increasing interest within the profession as this is likely to have implications for retention and attrition. Newly qualified midwives have reported that the reality of putting knowledge into practice in the midwifery field is often challenging and stressful.Aim: To explore and describe the experiences of newly qualified midwives with regard to the provision of midwifery services during transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The unfriendly ones give bad and demotivating remarks when we seek for assistance. It’s bad” ( 19 ). “…fter you have had handover and they are like, ‘Oh fine, do not worry.’ Then they go to the desk and they are like: ‘I do not want to come on to work after her, she leaves everything for the night staff” ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…The unfriendly ones give bad and demotivating remarks when we seek for assistance. It’s bad” ( 19 ). “…fter you have had handover and they are like, ‘Oh fine, do not worry.’ Then they go to the desk and they are like: ‘I do not want to come on to work after her, she leaves everything for the night staff” ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, patients disclosed that midwives insult and physically assault them, which explains the violation of their human rights. A study conducted in South African maternity settings reported that, globally, women experience ill-treatment in a pattern of physical abuse, verbal abuse, procedures without consent, neglect, non-confidential care and abandonment of care [ 26 ]. Similarly, a study conducted in Durban, South Africa, revealed that women described ill-treatment as verbal abuse from midwives, lack of privacy and midwives refusing to provide care [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the time experienced midwives took to orientate the new midwife increased workload, and patient care was also neglected (32). Furthermore, the orientation of the novice midwife directly affected the novice midwife as they felt unsupported, and this affected their con dence level in taking care of pregnant and labouring women (32).…”
Section: Sub-theme 12: Training and Orientating The Novice Midwifementioning
confidence: 99%
“…Another study reported that the time experienced midwives took to orientate the new midwife increased workload, and patient care was also neglected (32). Furthermore, the orientation of the novice midwife directly affected the novice midwife as they felt unsupported, and this affected their con dence level in taking care of pregnant and labouring women (32). These ndings are supported by Simane-Netshisaulu (33), who added that due to increased workload, midwives developed tension and a negative attitude towards the novice midwives, contributing to the unhealthy work environment.…”
Section: Sub-theme 12: Training and Orientating The Novice Midwifementioning
confidence: 99%